Influência do relevo e erodibilidade nos atributos químicos em área degradada de Gilbués, PI - Branco, Savio B. C.; Salviano, Adeodato A. C.; Matias, Sammy S. R.; Marques Jr., José [UNESP]; Santos, Hélio L. (Revista Brasileira de Ciencias Agrarias, 2013)
Soil degradation can be defined as a process that reduces the ability of soil to produce property or services. Thus, the objective was to study the influence of topography and erodibility in the distribution of the chemical attributes of an Alfissol in degraded areas of Gilbués in the State of Piaui, Brazil. In the chosen area a sampling grid of 1 ha was demarcated, with points spaced at 10 x 10 m, and 121 samples were collected at intersections, in 0-0.20 m depth. Each point was georeferenced as a way to demarcate the area and prepare a topography map. For all samples pH, organic matter, phosphorus, potassium, calcium, magnesium, hydrogen and aluminum were determined. The estimate of erodibility was calculated from the equation proposed by Denardin. Based on the experiment and the results obtained it is concluded that the number of samples used was sufficient to determine the variability of soil in degraded areas of the Gilbués municipality. The discontinuity in the topography of the landscape and erodibility cause a moderate degree of heterogeneity in most chemical properties of the studied soil, establishing specific management zones.
Influence of topography and erodibility in chemical properties in a degraded area of Gilbués, PI-Brazil
Keywords: Landscape; Soil; Spatial variability